Implemantasi Kebijakan Pembelajaran Berbasis Daring di SMP Muhammadiyah Kota Yogyakarta - Dian Hidayati; Arief Kurniawan; Susamta Susamta; Beny Setyawan (Universitas Pendidikan Indonesia, 2022)
This study aims to describe and provide advice on the implemen-tation of online-based learning policies at 2 Muhammadiyah Junior High Schools in Yogyakarta City. The research method used is qualitative, which was conducted by observation, interviews, documentation, and data triangulation. The result of the study is that the implementation of educational policies carried out by SMP Muhammadiyah is going well by preparing and carrying out the learning process by planning, organizing, and evaluating all activities carried out. The Ministry of Education and Culture of the Republic of Indonesia issued a Circular on the Implementation of Education Policy in the Emergency Period of the Spread of Coronavirus Disease (COVID-19) concerning the learning process from home which is carried out with the following provisions: (a) Learning from home provide a meaningful learning experience for students, without being burdened with completing the curriculum for grade promotion or graduation; (b) Learning from home can get education in life education; (c) activities and tasks according to their respective interests and conditions, including considering access/facilities for studying at home; (d) Evidence or products of learning activities from home are given qualitative and useful feedback from the teacher, without being required to provide a quantitative score/value.